2016
DOI: 10.1039/c5cp07817b
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Au–S complexes on Au(100)

Abstract: Using a combination of scanning tunneling microscopy and density functional theory (DFT) calculations, we have identified a set of related Au-S complexes that form on Au(100), when sulfur adsorbs and lifts the hexagonal surface reconstruction. The predominant complex is diamond-shaped with stoichiometry Au4S5. All of the complexes can be regarded as combinations of S-Au-S subunits. The complexes exist within, or at the edges of, p(2 × 2) sulfur islands that cover the unreconstructed Au regions, and are observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 63 publications
1
27
0
Order By: Relevance
“…However, for the samples of MoS 2 on NPG, the Mo/S ratios are all less than 0.5, suggesting the existence of excess sulfur in the system. Combined with the facts that the covalent bond between gold and sulfur could form 26,27 , the XPS results suggest the possible formation of the Au-S bonding after MoS 2 growing on NPG.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…However, for the samples of MoS 2 on NPG, the Mo/S ratios are all less than 0.5, suggesting the existence of excess sulfur in the system. Combined with the facts that the covalent bond between gold and sulfur could form 26,27 , the XPS results suggest the possible formation of the Au-S bonding after MoS 2 growing on NPG.…”
Section: Resultsmentioning
confidence: 82%
“…Although Au is inert in bulk form, Au surface atoms has rich ligand chemistry partially due to the existence of possible oxidation states of gold. Various Au-thiolate complexes and low-temperature chemisorbed sulfur have been observed on Au surfaces 26,27 . Accordingly, the vapored sulfur and S-Mo precursors formed during CVD reactions may affect the atomic structures of gold surfaces and, subsequently, alter interfacial interactions with as-deposited 2D TMDs.…”
mentioning
confidence: 99%
“…In contrast to Cu and Ag, for Au surfaces exposed to S, no complexes were observed by LTSTM on Au(111), 16 but an Au 4 S 5 complex and fragments of this complex were found on Au(100). 17 Motivated by dramatic enhancement of mass transport for Cu(111) and Ag(111) exposed to trace amounts of S, 2,6 previously Density Functional Theory (DFT) analyses was undertaken to assess stability of various M-S complexes on M(111) surfaces for M = Cu and Ag. The first such DFT study considered Cu 3 S 3 on Cu(111) which was proposed to facilitate accelerated transport across the Cu(111) surface.…”
Section: Introductionmentioning
confidence: 99%
“…Elsewhere, we have reported that (near-)linear S-M-S units are structural motifs of complexes that form between S and coinage metals M on the Cu(111), Ag(111), and Au(100) surfaces. 16,18,20,51,52 In the case of CuS 2 complexes, we showed that the linear geometry was favored because it maximized the overlap between S porbitals and Cu-d z 2 orbitals. 20 The linearity of X-M-X units may provide an explanation for the different relative stabilities of R-A2 for O and S. In the double-row structures, there is an interaction ∆ between adsorbates, based on the fact that µ O of the double-row is always different than the average of the constituent single-row structures.…”
Section: Discussionmentioning
confidence: 79%
“…Our confidence in the results from the present DFT calculations is based largely on past successes with adsorption of chalcogens on coinage metals, where detailed comparisons with high-quality experimental data served to indicate the successes or shortcomings of DFT. [14][15][16][17][18][19][20][21] Most notably, DFT successfully provided an interpretation of scanning tunneling microscopy (STM) data for sulfur adsorption and sulfurinduced reconstruction at steps on Cu(111), 18 for seleniuminduced faceting of steps on Cu(111), 15 and for adsorption of sulfur atoms at steps (without reconstruction or faceting) on Cu(100). 14 Various aspects of the experimental dataadsorption sites, coverage dependence, and image featureswere consistent with DFT results.…”
Section: Introductionmentioning
confidence: 99%